Rosa mironovae, a new replacement name for R. mutabilis N.V. Mironova (Rosaceae) (Bangladesh Journal of Plant Taxonomy, 2023)
Abstract not Available.Bangladesh J. Plant Taxon. 30(1): 165-169, 2023 (June)